THE EFFECT OF INTEGRATED MARKETING COMMUNICATION, SERVICE QUALITY, AND CONSUMER BEHAVIOR TOWARDS ONLINE PURCHASE DECISIONS ON THE SHOPEE APPLICATION (Study On Students Of The Faculty Of Economics, Universitas Islam Lamongan) - Fidianatus Sholikha; Titin Titin; Luluk Nur Azizah (Sean Institute, 2023)
The purpose of this research is to find out whether integrated marketing communication (X1), service quality (X2) and consumer behavior (X3) on purchasing decisions (Y) in the study shopee application for students of the economics faculty of the Islamic University of Lamongan . The test results show that: T-test of Integrated Marketing Communication variable obtained Tcount (5,727) > Ttable (1,970), Service Quality variable obtained Tcount (3,061) > Ttable (1,970), Consumer Behavior variable obtained from Tcount (4,255) > Ttable (1970). Test Fcount (80.109) > Ftable (2.65). From the multiple linear regression test Y = 4.224 + 0.348 + 0.183 + 0.362, it can be seen that the most dominant value is Consumer Behavior of 0.362. The most dominant variable from the research is consumer behavior (X3).